1992
DOI: 10.1128/iai.60.2.416-427.1992
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expression of a gene which encodes a wall-associated proteinase of Coccidioides immitis

Abstract: A chymotrypsinlike serine proteinase of Coccidioides immitis with an estimated molecular size of 34 kDa has been shown by immunoelectron microscopy to be associated with the walls of the parasitic cells of this human respiratory pathogen. The proteinase has been suggested to play a role in spherule development. We report the isolation of a 1.2-kb cDNA from an expression library of C. immitis constructed in the XZAP II phage vector. The cDNA is suggested to encode the 34-kDa protein. We demonstrate identity bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The gene encoding this serine proteinase has been cloned and sequenced, and its B-cell epitopes were expressed on a fusion protein encoding a portion of the mature enzyme (48). The open reading frame of the gene predicts a protein of 34.3 kDa, which is in agreement with the 36 kDa observed on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels.…”
Section: Coccidioides Immitissupporting
confidence: 61%
See 1 more Smart Citation
“…The gene encoding this serine proteinase has been cloned and sequenced, and its B-cell epitopes were expressed on a fusion protein encoding a portion of the mature enzyme (48). The open reading frame of the gene predicts a protein of 34.3 kDa, which is in agreement with the 36 kDa observed on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels.…”
Section: Coccidioides Immitissupporting
confidence: 61%
“…The association of the proteinase with mycelia and conidia suggests that it may be released from outer cell wall of conidia soon after inhalation, leading to immediate damage of respiratory tract tissue (323). Immunoelectron microscopy with rabbit monospecific antiserum against purified proteinase detected the proteinase in the cell walls of mycelia and spherules, in the segmentation apparatus of the developing spherule (324), and in close association with chitin in the presegmentation spherule (48). The density of the proteinase in the segmentation apparatus suggests that one likely role of the proteinase in the fungal life cycle is to promote the dissolution of the wall matrix and segmentation apparatus as the endospores mature.…”
Section: Coccidioides Immitismentioning
confidence: 99%
“…The suggested molecular size of the purified proteinase was 34 kDa. The enzyme was localized in the walls of parasitic cells of C. immitis (immunoelectron microscopic studies) (63). In 1992, Cole et al also reported isolation and expression of the gene that encoded the enzyme (63).…”
Section: Scientific Contributionsmentioning
confidence: 99%
“…The highest enzyme activity was observed in the presence of presegmented spherule wall material. The first-generation spherules (strain C735) from which this wall fraction was obtained were incubated for approximately 36 h in modified liquid Converse medium and were nearly synchronized in their early diametric growth phase (9). Wall preparations in the absence of ,B-glucosidase showed no glucose release.…”
Section: Monosacfharide Compositionmentioning
confidence: 99%
“…Certain of these isolated cell wall-associated antigens (Ags) also demonstrate proteolytic activity (10). Proteinases expressed by the parasitic phase have been suggested to play roles in spherule development and endosporulation as well as host tissue invasion and destruction (9,32).…”
mentioning
confidence: 99%